Better outcomes for everybody evaluates the effectiveness and cost-effectiveness of a pharmacist-led intervention, delivered by community pharmacists in collaboration with physicians, in improving disease control, compared with usual care, in asthma and COPD patients during and after COVID-19: a protocol for a pragmatic, parallel randomised controlled trial - Manfrin, A; Jackson, C; Campisi, R; Oteri, A; Copani, A; Desideri, E; Tsiachristas, A; Candio, P; Di Tomaso, G; Vitale, M; Crimi, N (Wolters Kluwer Health, 2021)
Introduction: In 2025, more than 400 million people will have asthma, and chronic obstructive pulmonary disease (COPD) will be the third leading cause of death by 2030. This trial, called better outcomes for everybody, will evaluate the effectiveness and cost-effectiveness of a pharmacist-led intervention delivered by community pharmacists in collaboration with physicians to asthma and COPD patients to improve disease control compared with usual care.